Effects of treatment with methimazole on circulating CD4+ and CD8+ T cells positive for programed cell death protein‐1 and on subsets of CD4+ T cells in untreated hyperthyroid patients with Graves' disease. (17th June 2022) - Hirao, Nanako; Iijima, Toshie; Tanuma, Dai; Ohira, Eriko; Kurai, Hidetaka; Shinzawa, Toshimitsu; Kase, Masato; Sakurai, Shintaro; Tomaru, Takuya; Jojima, Teruo; Usui, Isao; Aso, Yoshimasa
Abstract: Objective: We investigated longitudinal changes in circulating CD4 + and CD8 + T cells positive for programed cell death protein‐1 (PD‐1) and in other subsets of CD4 + T cells in untreated hyperthyroid patients with Graves' disease after treatment with methimazole (MMI). Design and Patients: The study included 18 untreated hyperthyroid patients with Graves' disease and 18 age‐matched controls. Before and after 12‐week treatment with MMI, we used flow cytometry to measure circulating PD‐1 +  D4 + and PD‐1 + CD8+ T cells and subsets of CD4 + T cells in peripheral blood, as well as serum levels of chemokines related to T‐helper type 1 (Th‐1) and Th‐2 cells. Results: At baseline, the percentage of CD4 + and CD8 + T cells expressing PD‐1 was significantly higher in patients than in age‐matched controls. Serum levels of chemokines related to Th‐1 and Th‐2 also were higher in patients. Twelve weeks after initiation of MMI, the percentage of CD4 + T cells expressing PD‐1 was significantly lower than at baseline, but no such change was seen in CD8 + T cells. Furthermore, the percentage of Th‐1 cells among CD4 + T cells and the serum levels of soluble CD26/dipeptidyl peptidase‐4, a surface marker of Th‐1 cells, also were significantly lower than at baseline. Conclusions: The expression of PD‐1 on circulating CD4 + and CD8 + T cells is increased in hyperthyroid patients with active Graves' disease. MMI significantly decreases levels of circulating PD‐1 +  CD4 + T cells, suggesting that PD‐1 + T lymphocytes may be associated with the pathogenesis of Graves' disease.